A short and efficient protocol for the synthesis of imidazo[1, 5-a]quinoxalin-4-ones from 3-aroylquinoxalinones and compounds with the aminomethylene moiety. Issue 1 (7th January 2015) - Mamedov, Vakhid A.; Kalinin, Aleksey A.; Zhukova, Nataliya A.; Syakaev, Victor V.; Rizvanov, Il'dar Kh.; Latypov, Shamil K.; Sinyashin, Oleg G.
Abstract The reaction of 3-aroylquinoxalin-2(1H)-ones with α-amino acids and their derivatives, amines with various alkyl groups, amino alcohols with alkylene groups of various length, N-(3-aminopropyl)morpholine and 1, 6-diaminohexane in DMSO at 150 °C proceeds through the oxidative cyclocondensation and makes it possible to synthesize substituted imidazo[1, 5-a]quinoxalines. Depending on the compound with the aminomethylene fragment used the reaction allows to introduction of any given substituent into position 1.